2012
DOI: 10.1158/1055-9965.epi-11-0981
|View full text |Cite
|
Sign up to set email alerts
|

Urinary 8-Oxoguanine as a Predictor of Survival in Patients Undergoing Radiotherapy

Abstract: Background: Because of the importance to identify prognostic indicator for radiotherapy, herein we decided to check whether the parameters which describe oxidative stress/DNA damage may be used as a marker of the therapy. The aim of this work was to investigate whether fractionated radiotherapy of patients with cancer (n ¼ 99) is responsible for oxidative DNA damage on the level of the whole organism and whether the biomarkers of the damage such as 8-oxo-7,8-dihydro-2 0 -deoxyguanosine (8-oxo-dG) and its modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
(11 reference statements)
0
19
0
Order By: Relevance
“…In biological systems, oxidative stress is formed as a result of an imbalance between the production and the elimination of reactive oxygen species toward the creation of the ROSs [1]. This reaction is considered a critical process in many diseases, including cancer and Alzheimer's [2‐4]. Among various oxidative stress products, 8‐oxo‐deoxyguanosine formed as a result of the reaction of ROS with DNA [1,5‐8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In biological systems, oxidative stress is formed as a result of an imbalance between the production and the elimination of reactive oxygen species toward the creation of the ROSs [1]. This reaction is considered a critical process in many diseases, including cancer and Alzheimer's [2‐4]. Among various oxidative stress products, 8‐oxo‐deoxyguanosine formed as a result of the reaction of ROS with DNA [1,5‐8].…”
Section: Introductionmentioning
confidence: 99%
“…These two compounds are frequently used as biomarkers for oxidative stress and DNA damage. Following their formation, in intracellular media, they are transported to extracellular media and blood, and then to saliva and urine [2,4,9,10]. Therefore, the last two matrices are frequently considered for the determination of oxidative stress biomarkers [24, 913].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] Abnormal levels of nucleobases and their metabolites reflect disorders in nucleic acid metabolism which leads to av ariety of diseases,s uch as cancer, immunodeficiency, aging,k idney diseases,g out, and several mitochondrial pathologies. [6] 8-Oxo-2'-dG and 8-Oxo-2'-G have also being regarded as molecular markers of cancer. [4] It has been shown that nuclear oxidative damage is associated with poor survival in colorectal cancer [5] and urinary 8-Oxo-2'-dG has been used as apredictor of survival in patients treated with radiotherapy.…”
mentioning
confidence: 99%
“…[4] It has been shown that nuclear oxidative damage is associated with poor survival in colorectal cancer [5] and urinary 8-Oxo-2'-dG has been used as apredictor of survival in patients treated with radiotherapy. [6] 8-Oxo-2'-dG and 8-Oxo-2'-G have also being regarded as molecular markers of cancer. [7] Ther apid proliferation of tumor cells correlates with as ignificantly higher cellular concentration of nucleotides,i ncluding GTP.O nt he other hand, guanine nucleotide depletion triggers cell cycle arrest and apoptosis.…”
mentioning
confidence: 99%